Fine Art and Design Works In the Context of Intellectual Property - Rahmanu Widayat; Deny Tri Ardianto (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2020)
Fine Art and design works are classified as Intellectual Property that is protected by law. On the other hand, art creations are prone to be imitated or falsified on the grounds of being taken as inspiration or for commercial advantage. In Higher Education, especially in the field of Art and Design, methods to create original works have been taught to prevent intelectual property violation. However, due to dishonorable interests, the possibility of plagiarism and forgery can still occur. The questions that arise were: 1) what are classified as works of art and design? 2) What are the Intellectual Property Laws related to the field of art and design? 3) What are the prevention methods offered by fine arts and design higher education? Interpretation method was applied on the law concerning art and design, complemented with an explanation of art and design work creation process as a form of prevention to avoid imitations.